Philippine anger and American conciliation: discourse and emotional diplomacy in the 2018 restitution of the Balangiga Bells - Enverga, Manuel R, III (Archīum Ateneo, 2022)
This paper is a case study on the restitution of the Balangiga Bells by the United States to the Philippines, which has been a decades-long contested issue in the two countries’ relations. This research applies the concepts of restitution, emotional diplomacy and discourse. This paper presents an exceptional instance in which the return of war trophies was achieved through bilateral arrangements rather than multilateral action. The approach examined how Philippine anger and American conciliation were presented as the two countries worked towards the Bells’ restitution. This paper examined public statements made by officials expressing their governments’ official positions. The researchers viewed their remarks as forms of discursive articulation, and analyzed them following Wodak’s Discourse Historical Approach. The paper’s focus moved beyond the surface level meanings of government officials’ statements, but also considered how the articulations were shaped by the context in which they were produced.